2012
DOI: 10.1007/s00580-012-1645-9
|View full text |Cite
|
Sign up to set email alerts
|

Histological and histometrical evidences for phenol immunotoxicity in mice

Abstract: Phenol is a common industrial and ubiquitous environmental chemical which is used to synthesize resins and plastics. Due to its anesthetic and disinfectant properties, phenol is also widely used in pharmaceutical products. Since there were no adequate data about phenol immunotoxicity, the purpose of the present study is to investigate its toxic effects on the histological structures of the lymphoid organs in the mice. A total of 80 mice were randomly distributed into one control group and three experimental gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This was in agreement with what is reported in many animal species including rat (Rosol et al, 2001;Wan Ezumi et al, 2007) and mouse (Di Curzio and Goldowitz, 2011;Monfared et al, 2014). Although physiological studies have shown that the secretion of adrenal chromaffin cell is mediated by cholinergic agonists (Douglas and Poisner, 1965;Unger and Philips, 1983;De Diego, 2010), attempts to develop immunohistochemical markers for the identification of cholinergic neurons have presented several difficulties.…”
Section: Discussionsupporting
confidence: 91%
“…This was in agreement with what is reported in many animal species including rat (Rosol et al, 2001;Wan Ezumi et al, 2007) and mouse (Di Curzio and Goldowitz, 2011;Monfared et al, 2014). Although physiological studies have shown that the secretion of adrenal chromaffin cell is mediated by cholinergic agonists (Douglas and Poisner, 1965;Unger and Philips, 1983;De Diego, 2010), attempts to develop immunohistochemical markers for the identification of cholinergic neurons have presented several difficulties.…”
Section: Discussionsupporting
confidence: 91%
“…Immunotoxicity may parallel alterations in the weight of lymphoid organs and/or changes in the normal microscopic architecture [37]. However, splenic immunosuppression may attribute to the decreased lymphatic cells numbers in the spleen and other immune organs [37,38]. Meneze sand colleagues [39] indicated that all extensive injuries were repaired with collagen fibers which may lead to the fibrosis as observed here.…”
Section: Discussionmentioning
confidence: 76%
“…Preclinical investigations have documented central nervous system depression and hepatic changes following PGMEA exposure, which quickly hydrolyzes to PGME upon absorption (Domoradzki, Brzak, & Thornton, ; OECD, , ; Spencer et al., ; U.S. Environmental Protection Agency [U.S. EPA], ). Phenol and cresol are known to target skin and mucosal membranes, in addition to their potential immunotoxic effects (Agency for Toxic Substances and Disease Registry [ATSDR], 2007a, , ; Hoffman et al., ; Louei Monfared, Jaafari, & Sheibani, ; Sanders et al., ; U.S. EPA, ). Chronic benzene exposure is associated with hematotoxicity, including anemia and leukopenia, as well as leukemia (ATSDR, ; Bayliss, Jinot, & Sonawane, ; Lan et al., ; U.S. EPA, ).…”
Section: Methodsmentioning
confidence: 99%